2022
DOI: 10.3390/medicina58121824
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential Use of Wearable Devices as a Prognostic Tool among Patients in Hospice Care

Abstract: Background—Smartphones and wearable devices have become a part and parcel of the healthcare industry. The use of wearable technology has already proved its potentials in improving healthcare research, clinical work, and patient care. The real time data allow the care providers to monitor the patients’ symptoms remotely, prioritize the patients’ visits, assist in decision-making, and carry out advanced care planning. Objective—The primary objective of our study was to investigate the potential use of wearable d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…The results of our current study are in line with our previous related study results, including two prospective observational studies [ 28 , 29 ] and a scoping review [ 44 ]. One of our previous findings showed that the majority of the included studies in the scoping review, which utilized wrist-worn wearable devices in cancer populations, focused on physical activity, sleep analysis, and heart vital signs and showed a positive correlation between patient-reported and wearable outcomes [ 44 ], while in the other study, automatic survival prediction using an LSTM DL model showed feasibility in clinical settings and possible benefits in end-of-life care settings without healthcare professionals [ 29 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The results of our current study are in line with our previous related study results, including two prospective observational studies [ 28 , 29 ] and a scoping review [ 44 ]. One of our previous findings showed that the majority of the included studies in the scoping review, which utilized wrist-worn wearable devices in cancer populations, focused on physical activity, sleep analysis, and heart vital signs and showed a positive correlation between patient-reported and wearable outcomes [ 44 ], while in the other study, automatic survival prediction using an LSTM DL model showed feasibility in clinical settings and possible benefits in end-of-life care settings without healthcare professionals [ 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…One of our previous findings showed that the majority of the included studies in the scoping review, which utilized wrist-worn wearable devices in cancer populations, focused on physical activity, sleep analysis, and heart vital signs and showed a positive correlation between patient-reported and wearable outcomes [ 44 ], while in the other study, automatic survival prediction using an LSTM DL model showed feasibility in clinical settings and possible benefits in end-of-life care settings without healthcare professionals [ 29 ]. Additionally, in the third study, wearable devices reported greater angle and spin movements as early as within the first 48 h of observation in the cancer patients who were still alive after discharge from the hospice inpatient unit [ 28 ]. Based on our previous research findings that showed the potential of wearable devices and the utility of actigraphy data as a prognostic tool for patients in hospice care, the current study builds on the concept of utilizing wearable data to predict survival outcomes in hospice patients [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of proxies to help measure patient‐reported outcome measures also may hold some promise for PLWD if viewed as complementary rather than substitutive 66,67 . Emerging data capture methods such as natural language processing (NLP) to measure ACP documentation, patient portals to measure electronic PCROs along with wearable devices, smartphones, and artificial intelligence to help measure prognosis and patient‐related parameters may also yield future highly pragmatic outcome measures 51,68–72 . In ADRD pragmatic trials conducted in the home or community setting, a multi‐level approach will likely need to be considered for the collection of PCROs in the absence of healthcare records or administrative data collection methods 73 …”
Section: Discussionmentioning
confidence: 99%